2017
DOI: 10.1117/1.jatis.3.3.035002
|View full text |Cite
|
Sign up to set email alerts
|

Complex spectral line profiles resulting from cryogenic deformation of the SINFONI/SPIFFI diffraction gratings

Abstract: Abstract. The integral field spectrograph, spectrometer for infrared faint field imaging (SPIFFI), has complex line profile shapes that vary with wavelength and pixel scale, the origins of which have been sought since the instrument construction. SPIFFI is currently operational as part of SINFONI at the Very Large Telescope (VLT) and will be upgraded and incorporated into the VLT instrument enhanced resolution imager and spectrograph (ERIS). We conducted an investigation of the line profiles based on the measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It was found that the interplay of the lightweighting structure with the stress induced by the NiP coating at cryogenic temperatures caused deformations of the grating surface and led to degraded instrumental line profiles. 12 The new gratings of SPIFFIER are based on Zerodur blanks without any lightweighting and, therefore, substantially improve the shapes of the spectral lines. Since line profiles are undersampled on the detector (the widths are less than two pixels), an approach similar to 13 was used to obtain hypersampled spectral line profiles for the detailed line-shape analysis.…”
Section: Instrumental Line Profilesmentioning
confidence: 99%
“…It was found that the interplay of the lightweighting structure with the stress induced by the NiP coating at cryogenic temperatures caused deformations of the grating surface and led to degraded instrumental line profiles. 12 The new gratings of SPIFFIER are based on Zerodur blanks without any lightweighting and, therefore, substantially improve the shapes of the spectral lines. Since line profiles are undersampled on the detector (the widths are less than two pixels), an approach similar to 13 was used to obtain hypersampled spectral line profiles for the detailed line-shape analysis.…”
Section: Instrumental Line Profilesmentioning
confidence: 99%
“…When they are cooled, this leads to an 'eggbox' structure that mimics a grating. 36 The gratings will be replaced when SPIFFI is refurbished as SPIFFIER and integrated into ERIS.…”
Section: Spiffier Integral Field Spectrographmentioning
confidence: 99%
“…9 shows, the rationale for the latter step is that the light-weighting of the current gratings leads to an 'eggbox' deformation when cooled, which acts as an an additional grating and leads to a complex spectral profile. 36 With new collimator mirrors and gratings, as well as filters (those installed in 2016 have a throughput exceeding 98% across the full band 35 ), the sensitivity is expected to increase by a significant factor. In addition, the entrance window will be replaced by a smaller one matched to the nominal field (since the sky spider has been removed), and the pre-optics collimator will be replaced to accommodate the new AO optical interface.…”
Section: Spiffier Integral Field Spectrographmentioning
confidence: 99%